Seismic analysis of the Onshore Mozambique Basin Reservoirs, Inhassoro Area - Mbatha, Bonginkosi Wiseman (University of the Witwatersrand, Johannesburg, 2025)
The Mozambique Basin has proven to be rich in hydrocarbon resources, with gas production since 2004. Exploration in this basin has, in the past, focused mainly onshore and centred around the Pande, Temane, and Inhassoro gas and oil fields. The use of amplitude characterization has assisted explorers in identifying gas accumulations, especially the stratigraphically trapped gas in Pande and Temane. The hydrocarbon-rich reservoirs in this basin are those mainly of the Lower Grudja Formation. These are Maastrichtian to Campanian aged reservoirs in the Late Cretaceous period. Seismic attributes can be used to understand these formations and their fluid content. Amplitude-based attributes have been studied successfully in the central part of the basin where the Lower Grudja Formation is relatively thick and, in some parts, saturated with hydrocarbon pore fluids. The study makes use of recently acquired high-resolution three-dimensional (3D) surface seismic data and well data information to characterize Mozambique Basin Lower Grudja reservoirs. Before the acquisition of the 3D seismic data, interpreters mainly relied on qualitative interpretation of 2D seismic surveys following anomalous amplitude events across seismic sections. The 2D seismic data had many limitations, including wide (2-4 km) line spacing, relying on projections from gridding algorithms. Attributes from seismic amplitudes extracted from stacked data can lead to misinterpretation, often referred to as false positives, and the drilling of dry holes. The study looks at the fundamental causes of these anomalous amplitude events. This implies that direct hydrocarbon indicators (DHI) require further analysis before being confirmed as representing hydrocarbon fluid-filled porous reservoirs. This is achieved through analysis of stacked seismic data (full and variable angle data), post-stack migrated data, pre-stack seismic gather data, and well information. Three main questions are investigated to quantitatively describe Mozambique Basin reservoirs: Rock Physics Modelling - is there a unique response due to changes in fluid composition in the subsurface that can be characterized using seismic data? Amplitude Variation with Offset (AVO) analysis – are these changes uniquely related to changes in fluid composition, or are they coupled with other reservoir and bounding rock properties? Seismic inversion – can we quantitatively predict the distribution of hydrocarbons across the Inhassoro block using both seismic attributes and quantitative interpretation methods? Pande seismic analysis and inversion of lower Grudja facies demonstrate that existing seismic gathers could be conditioned and made AVO compliant. This enables the determination of the AVO behaviour of Lower Grudja reservoirs, in this case, Pande G6 and G10. These reservoirs, owing to their high porosity gas sands capped by a relatively stiff rock, exhibit a class IV AVO response. True AVO class of Lower Grudja reservoirs is revealed when extracted from conditioned seismic gathers. This is complemented by intercept and gradient crossplots. AVO synthetics from wells with reliable well log data help model the expected AVO behaviour of Lower Grudja reservoirs. Quantitative analysis was also conducted in Temane and Inhassoro and included AVO modelling based on fluid and saturation scenarios. Crossplotting of elastic properties with petrophysical parameters concluded that bulk density is a proxy for relative porosity and relative fluid saturation, and shear modulus is a proxy for relative shale volume.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2025
Keywords: Seismic analysis; Mozambique basin; Amplitude characterisation; Seismic attributes; Direct hydrocarbon indicactors; Amplitude variation with offset; UCTD; SDG-7: Affordable and clean energy; SDG-13: Climate action